Framing Petroleum Revenue Management Law For Energy Sector Reform In Nigeria - Amadi, Law; Obutte, Peter Chukwuma (Journal of Sustainable Development Law and Policy, 2025)
This article considers the introduction and conceptual frameworks for petroleum revenue management law with a view to applying it in Nigeria. It examines the sources of petroleum revenue to enhance assessment and collection. The article examines the structure of the legislation and institutions regulating the petroleum sector by categorizing and highlighting the subset of petroleum revenue management for efficient application. It further argues that prudent management of petroleum revenue is measured through the indicators of transparency and accountability, sustainable development, sovereign wealth fund, low corruption level, socio-economic well-being, good health and sustainable environment. This article is imperative in that it streamlines the legislation and institutions, block revenue leakages and guarantee sustainable development. It will further ensure that revenue generated from petroleum resources is properly utilized for socio-economic growth of the nation. It urges the National Assembly to enact a law that will harmonize the diverse legislation and institutions and cause them to operate strictly in accordance with the principles of good governance, transparency and accountability.